Positive childhood experiences and burnout among medical students: the role of adaptive emotion regulation as a mediator - Lloyd, Rachel; Izad, Tina; Nazmifar, Michael; Walkon, Lauren; Mohiyeddini, Changiz (Frontiers in Psychology, 2026)
Burnout is a state of chronic exhaustion caused by excessive stress. Medical trainees are highly vulnerable to burnout, which can negatively affect their well-being. Empirical evidence from Bethell et al. demonstrates that positive childhood experiences reduce adult depression and anxiety, while Gross’s process model suggests that adaptive emotion regulation strategies buffer against stress-related outcomes. Building upon these frameworks, positive childhood experiences (PCE) and adaptive (positive) emotion regulation (ER) are thought to be protective against burnout, but the mechanisms which mediate these effects are poorly understood. This study aimed to explore whether adaptive ER mediates the relationship between PCE and burnout among medical students. Participants completed well-established and validated measurements of PCEs (Benevolent Childhood Experiences scale), adaptive ER (Cognitive Emotion Regulation Questionnaire short version), and burnout (Maslach Burnout Inventory). Our results indicate that adaptive ER mediates the relationship between PCEs and burnout, with a moderate indirect effect of PCEs on burnout (β = −0.31, accounting for approximately 67% of the total effect). These findings suggest that targeted intervention programs aiming to strengthen adaptive ER could help protect medical students against burnout. However, limitations include the cross-sectional design precluding casual inference, reliance on self-reported data, and recruitment from a single institution with predominantly female participants, which may limit generalizability to other medical schools.